2020
DOI: 10.3389/fcell.2020.582255
|View full text |Cite
|
Sign up to set email alerts
|

Coding Variants Coupled With Rapid Modeling in Zebrafish Implicate Dynein Genes, dnaaf1 and zmynd10, as Adolescent Idiopathic Scoliosis Candidate Genes

Abstract: Adolescent idiopathic scoliosis (AIS) is the most common pediatric spine disorder affecting ∼3% of children worldwide. Human genetic studies suggest a complex polygenic disease model for AIS with large genetic and phenotypic heterogeneity. However, the overall genetic etiology of AIS remains poorly understood. To identify additional AIS susceptibility loci, we performed whole-exome sequencing (WES) on a cohort of 195 Southern Chinese AIS patients. Bioinformatics analysis identified 237 novel rare variants asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…While scoliosis occured rarely in quadrupedal animals, the longitudinal shape of zebrafish coupled with their ability to experience spinal loads in water make them naturally sensitive to three-dimensional spine deformities, which they even naturally develop with elderliness, highly similarly to humans 15 , 16 . Recent studies have demonstrated a link between spinal curves and cilia motility involved in cerebrospinal fluid (CSF) circulation 11 13 , 17 , 18 , as mutants defective in cilia motility develop AIS phenotypes. A cilium-linked physiopathology in AIS patients is highly suspected, as mutations related to cilium has been found in AIS cohorts (POC5, PAX1) and due to the correlation between CSF-flow and AIS illustrated by the higher prevalence of scoliosis in AIS patients 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…While scoliosis occured rarely in quadrupedal animals, the longitudinal shape of zebrafish coupled with their ability to experience spinal loads in water make them naturally sensitive to three-dimensional spine deformities, which they even naturally develop with elderliness, highly similarly to humans 15 , 16 . Recent studies have demonstrated a link between spinal curves and cilia motility involved in cerebrospinal fluid (CSF) circulation 11 13 , 17 , 18 , as mutants defective in cilia motility develop AIS phenotypes. A cilium-linked physiopathology in AIS patients is highly suspected, as mutations related to cilium has been found in AIS cohorts (POC5, PAX1) and due to the correlation between CSF-flow and AIS illustrated by the higher prevalence of scoliosis in AIS patients 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Cowden syndrome is a genetic condition characterized by a large head, hamartomatous lesions affecting derivatives of ectodermal, mesodermal, and endodermal layers, macrocephaly, facial trichilemmomas, and scoliosis [24,25]. The association of TNS1 with AO or KFS has not been previously reported, thus the present ndings may represent a novel disease association [26].…”
Section: Clinical Features and Radiographic Parameters Of The Cohortmentioning
confidence: 57%
“…Cowden syndrome is a genetic condition characterized by a large head size, facial trichilemmomas, and scoliosis. Wang et al reported that the TNS1 mutation may result in adolescent scoliosis in 2020 [26]. Mutations in FRFR2 have been previously associated with Pfeiffer and Crouzon syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, several studies have focused on discovering the genetic variants associated with AIS, either by identifying mutations that segregate with the disease or polymorphic loci in affected population studies. Thus, genome-wide association studies (GWAS) and whole exome sequencing (WES) have greatly contributed to understanding the etiology of AIS by identifying single nucleotide polymorphisms (SNPs) and gene variants in several loci, respectively ( Gao et al, 2007 ; Takahashi et al, 2011 ; Kou et al, 2013 ; Baschal et al, 2014 ; Ogura et al, 2015 ; Patten et al, 2015 ; Sharma et al, 2015 ; Zhu et al, 2015 ; Zhu et al, 2017 ; Khanshour et al, 2018 ; Kou et al, 2019 ; Liu et al, 2019 ; Wang et al, 2020 ; Terhune et al, 2021b ). These efforts have been pivotal to characterize genotype-AIS associations and expand our understanding of the genetic regulation behind scoliosis in humans.…”
Section: Human Adolescent Idiopathic Scoliosis: Genetics Of a Mysteri...mentioning
confidence: 99%
“…Therefore, and considering that humans are unsuitable for robust functional interrogation of the largely unknown functions of AIS-associated genes at large scale, there is a need for model systems that enable the generation of mutants to study genotype-phenotype interactions. Indeed, the function of AIS risk genes identified by GWAS and WES studies, including LBX1, DNAAF1, ZMYND10, MAPK7, KIF6, and PAX1, has successfully been studied in a vertebrate mutant system ( Figure 1A ) ( Adham et al, 2005 ; Guo et al, 2016 ; Gao et al, 2017 ; Konjikusic et al, 2018 ; Wang et al, 2020 ).…”
Section: Human Adolescent Idiopathic Scoliosis: Genetics Of a Mysteri...mentioning
confidence: 99%